2019
DOI: 10.3390/cells8090996
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate at the Vertebrate Neuromuscular Junction: From Modulation to Neurotransmission

Abstract: Although acetylcholine is the major neurotransmitter operating at the skeletal neuromuscular junction of many invertebrates and of vertebrates, glutamate participates in modulating cholinergic transmission and plastic changes in the last. Presynaptic terminals of neuromuscular junctions contain and release glutamate that contribute to the regulation of synaptic neurotransmission through its interaction with pre- and post-synaptic receptors activating downstream signaling pathways that tune synaptic efficacy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…In mammals, glutamate functions as the primary excitatory neurotransmitter in the CNS, while in Drosophila, ACh has this role. Conversely, flies use glutamate at the neuromuscular junction, while in mammals, that neurotransmitter is ACh (Colombo and Francolini, 2019). Although flies do have glutamatergic neurons in the CNS, their role has historically not been well-understood (Liu and Wilson, 2013); but recent advancements will be discussed below.…”
Section: Glutamatementioning
confidence: 99%
“…In mammals, glutamate functions as the primary excitatory neurotransmitter in the CNS, while in Drosophila, ACh has this role. Conversely, flies use glutamate at the neuromuscular junction, while in mammals, that neurotransmitter is ACh (Colombo and Francolini, 2019). Although flies do have glutamatergic neurons in the CNS, their role has historically not been well-understood (Liu and Wilson, 2013); but recent advancements will be discussed below.…”
Section: Glutamatementioning
confidence: 99%
“…Our study showed that in C. gigas larvae CgNOS as well as CgNR1 are both expressed in the foot, particularly near the foot base, supporting this theory of NMDA receptor regulating NO production via intracellular Ca 2+ concentrations and subsequent activation of CgNOS. Co-localisation of NMDA receptors and NOS in vertebrates mostly occur on the postsynaptic side or neuromuscular junctions [ 69 ]. Thus, CgNOS could receive signals from NMDA receptors for further downstream pathways potentially involved in regulating foot glands for cementation [ 47 – 49 ] or muscle fibres ([ 69 ], and references herein), both also located at the base of the foot [ 47 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-localisation of NMDA receptors and NOS in vertebrates mostly occur on the postsynaptic side or neuromuscular junctions [ 69 ]. Thus, CgNOS could receive signals from NMDA receptors for further downstream pathways potentially involved in regulating foot glands for cementation [ 47 – 49 ] or muscle fibres ([ 69 ], and references herein), both also located at the base of the foot [ 47 , 70 ]. Physical interaction between vertebrate transmembrane NMDA receptors and NOS, when not soluble in the cytosol, also exists via postsynaptic density proteins 95 (PSD-95), which binds to the PDZ domains of the NMDA receptor and NOS [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that in C. gigas larvae CgNOS as well as CgNR1, the NMDA receptor subunit 1, are both expressed in the foot, particularly near the foot base, supporting this theory of NMDA receptor regulating NO production via intracellular Ca 2+ concentrations and subsequent activation of CgNOS. Colocalisation of NMDA receptors and NOS in vertebrates mostly occur on the postsynaptic side or neuromuscular junctions (68). Thus, CgNOS could receive signals from NMDA receptors for further downstream pathways potentially involved in regulating foot glands for cementation (46)(47)(48) or muscle bres ( 68, and references herein), both also located at the base of the foot (46,69).…”
Section: Discussionmentioning
confidence: 99%